2013
DOI: 10.1027/1015-5759/a000130
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Polish Adaptation of the 11-Item De Jong Gierveld Loneliness Scale

Abstract: The aim of this study was to translate into Polish and establish the psychometric properties of the 11-item De Jong Gierveld Loneliness Scale (DJGLS). The translation process followed the recent guidelines for the crosscultural adaptation of questionnaires and was tested through analysis of differential item functioning (DIF) by the use of the Poly-SIBTEST method and bilingual groups. The essential unidimensionality was checked by bifactor analysis. Reliability was assessed by internal consistency and homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 91 publications
5
113
0
3
Order By: Relevance
“…In line with growing research, loneliness was highly correlated with depression (Cohen-Mansfield and ParpuraGill, 2007;Cukrowicz et al, 2011;Grygiel et al, 2012;Jaremka et al, 2012;Losada et al, 2012). This finding provides additional evidence to the studies that point out significant associations between loneliness and depression, and highlights the need to consider the measurement of loneliness for a better understanding of mental health in the elderly.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In line with growing research, loneliness was highly correlated with depression (Cohen-Mansfield and ParpuraGill, 2007;Cukrowicz et al, 2011;Grygiel et al, 2012;Jaremka et al, 2012;Losada et al, 2012). This finding provides additional evidence to the studies that point out significant associations between loneliness and depression, and highlights the need to consider the measurement of loneliness for a better understanding of mental health in the elderly.…”
Section: Discussionsupporting
confidence: 79%
“…In this regard, van Baarsen et al (2001) also highlighted the ambiguity of the social or emotional component of the items, thus making the examination of the internal structure of the scale more difficult. Similarly, Grygiel et al (2012) found that not all the positive items defined social loneliness and not all negative items defined emotional loneliness. Despite the presence of DIF we did not deeply examine it by means of different techniques other than the Rasch model.…”
Section: Limitations Of the Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, van Tilburg et al, (2004) recognized the possibility that negative items might measure social and emotional loneliness and that positive ones would only measure social loneliness. Grygiel et al (2012) also found the best fit for a bifactor model, which indicated that all items were related to a general feeling of loneliness. The correlation between the social and emotional factors was .77.…”
Section: Discussionmentioning
confidence: 99%
“…De Jong Gierveld i F. Kamphuis (1985), polska adaptacja P. Grygiel, G. Humenny, S. RĊbisz, P. ĝwitaj i J. Sikorska-Grygiel (2012), jest zasadniczo jednowymiarowa i mierzy zgeneralizowane poczucie samotnoĞci (zmienna zaleĪna). NarzĊdzie to składa siĊ z 11 twierdzeĔ i jest czĊĞciowo zbalansowane.…”
Section: Narzĉdziaunclassified